Great spotted cuckoos respond earlier to the arrival of feeding foster parents and perform less erroneous begging when hungry than their magpie host nest‐mates. (9th May 2019) - Soler, M.; de Neve, L.; Macías‐Sánchez, E.; Pérez‐Contreras, T.
Abstract : In many bird species, parents usually feed the first nestling that starts to beg before its nest‐mates. The pressure to avoid missed feeds could trigger nestlings to perform in erroneous begging in absence of parents, which has the same costs as begging in the presence of parents but without any reward. So, nestlings should try to minimize both erroneous begging and missed feeds simultaneously. The threshold to start begging is predicted to be lower for hungry nestlings and for nestlings that are unrelated to their nest‐mates, because they suffer lower inclusive fitness costs when depriving nest‐mates of food. In line with this idea, we found that brood parasitic great spotted cuckoo nestlings responded sooner than their magpie nest‐mates when an adult arrived to the nest. Under laboratory conditions, nestlings of both species rarely incurred in erroneous begging when food was abundant, but under conditions of restricted food, magpie nestlings increased erroneous begging while cuckoo nestlings did not. Highly conspicuous begging in cuckoos results in an increased predation risk, which could have resulted in stronger selection pressures on cuckoos to avoid erroneous begging, probably resulting in better developed perceptual abilities, allowing cuckoos to perform better than their host nest‐mates.